Optimum proportion of sweet corn by-product silage (SCW) and rice straw in total mixed ration using in vitro gas production - Kraiprom, Thaintip; Tumwasorn, Sornthep (Agriculture and Natural Resources, 2017)
An in vitro gas technique was used to study the effects of different proportions of sweet corn by-product silage (SCW) and rice straw (RS) on in vitro fermentation. The dietary treatments were ratios of SCW and RS all on a on a dry matter (DM) basis: T1 = SCW: RS at 60:40; T2 = SCW: RS at 50:50; and T3 = SCW:RS at 40:60. The ration of concentrate and roughage was 60:40 on a DM basis. The DM, crude protein (CP), ether extract (EE), acid detergent fiber (ADF) and neutral detergent fiber (NDF) of SCW were 22.56, 7.11, 1.89, 41.34 and 78.45%, respectively. The results showed that cumulative gas production at 48 h and 72 h after incubation with the ratio of SCW to RS at 60:40 on a DM basis was significantly (p < 0.05) higher than the results from the ratio of SCW to RS at either 50:50 or 40:60 on a DM basis. The proportion of SCW and RS among treatments had no effect on true digestibility parameters. However, the in vitro organic matter digestibility parameters in the treatment group with SCW:RS at 60:40 on a DM basis were higher (p < 0.05) than in the other two treatments. The total volatile fatty acid in the treatment group with SCW:RS at 50:50 and 40:60 on a DM basis were higher (p < 0.05) than in the treatment group with SCW:RS at 60:40 on a DM basis. Acetic acid (C2), propionic acid (C3) butyric acid (C4) and the proportion of C2:C3 were not different (p < 0.05) among treatments. The levels of NH3-N in all groups were not significant (p < 0.05) among treatments. It was concluded that the optimum level of SCW:RS was 60:40 on a DM basis.